Azorean fishers and policy decisions - Neilson, Alison (2020)
Drawing from long term social science research in the coastal fishing communities of the Azores archipelago, we highlight the ways that small-scale fishers are prevented from influencing policy decisions, in large part because of the way much science and public discourse excludes people from the ocean. In particular, we show how lack of consideration for gender not only leaves half of the population out of the discussions about fishing policy and coastal marine planning, but removes cultural, spiritual and other social values from being respected through planning processes and policies. We discuss our experiences in the islands and why we believe that trying to serve a just and sustainable socio-ecological well-being means that we need to engage with natural scientists to help identify the often hidden, but powerful ways that people are separated from the environment. We trace the way this powerful underlying people/ocean separation has influenced concepts of sustainable development and severely limits how ocean literacy is promoted at all levels from aquarium educators to policy decision-makers.